Potencial regenerativo de Cabralea canjerana (vell.) Mart. por condução de brotações em floresta secundária, RS - Alves, Vanessa Ferreira (2022)
The objective of this study was to determine the regenerative potential of Cabralea canjerana (vell.) Mart, by sprouting young plants in Deciduous Seasonal Forest in the Atlantic Forest biome, in a private area, in the locality of Val Feltrina Silveira Martins- RS. From a known population of C. canjerana, 25 regenerants with low stem quality were selected. All received a bevel cut, with a 10 and 15º angle, and the stubs were inspected monthly, removing the vines on the shoots. Measurements of sprout vigor were made as changes were identified during the inspections. The origin of the sprouts was also identified, and, at the end, their attachment to the stump was evaluated. For data analysis, the PROC GLM procedure was used for the variables, number of sprouts (NB), average height of sprouts (AB) and height of the largest sprout (AMB), where the analysis of covariance was applied as a function of time after cutting with effect of diameter classes of the stump. In addition, an analysis of variance was performed based on the data from the last evaluation to analyze the relationship of diameter of the base of the largest shoot (DMB) and height of the largest shoot (AMB) with the Classes of stub diameter (DT), and Classes of number of shoots, adding BOX PLOT plots. Stump diameter classes influenced the variables evaluated. NB was lower in stubs with diameters less than five centimeters, diverging from the others. AB and AMB were increasing with stub diameter, differing significantly in the three classes. AMB showed a positive linear relationship with DMB, without significant differences in the classes of stub diameter, as well as in the classes of number of shoots per stub, indicating that competition among shoots does not alter the AMB/DMB ratio, that is, a greater number of shoots per stub does not make them more slender. The attachment of shoots to the stub is efficient. The use of coppice is recommended for recovering young canjerana plants in secondary forests.